Transoral robotic surgery for hilo-parenchymal submandibular stones: step-by-step description and reasoned approach. Issue 12 (December 2019) - Capaccio, P.; Montevecchi, F.; Meccariello, G.; D'Agostino, G.; Cammaroto, G.; Pelucchi, S.; Vicini, C.
Abstract: The conservative transoral approach to hilo-parenchymal submandibular stones has been proposed as an alternative to traditional sialadenectomy. The main purpose is to preserve the gland and eliminate the risk of a cervical scar and damage to the marginal mandibular branch of the facial nerve. The spread of transoral robotic surgery has favoured its application not only in the oropharynx, but also in the anterior oral cavity. This article describes a transoral robotic approach for hilo-parenchymal submandibular stones. In January 2019, two patients with a right and a left hilo-parenchymal submandibular stone of 15 mm and 8 mm, respectively, underwent removal of the stone with transoral robotic surgery using the Si Da Vinci surgical robot. The procedure was performed successfully and tolerated well, with a one-night hospitalization. There were no complications such as lingual nerve damage, painful gland swelling, infection, or ranula. The patients were followed up clinically and ultrasonographically for the first 3 months to verify symptom relief and persistence of stones; no symptoms or stones were found. The transoral robotic surgical approach seems to be safe and adequate for the conservative management of large hilo-parenchymal submandibular stones. An adequate diagnosis together with proper docking and an appropriate approach to the oral floor is mandatory.